CO2 Adsorption Capacity of Organic Alkali Sorbent CPEI from Polyethyleneimine - Feng Wang; Lu Yu; Youhua Li; Dengfa Huang (Adsorption Science & Technology)
Support-free cross-linked polyethyleneimine sorbent (CPEI) for CO2 capture was evaluated as the regenerable sorbent. The total amines available for the CO2 capture on CPEI were determined by the polyethyleneimine/glutaraldehyde ratio for the synthesis of CPEI. The CO2 capacity of CPEI in the slurry bubble column reactor reached 4.92 mmol/g, which is 1.97 times higher than that obtained under anhydrous conditions. The adsorption kinetics of CPEI in the reactor were investigated in terms of the CPEI amount, the CO2 fraction, the gas flow rate, temperature, and the total amines available. The experimental breakthrough curves for the sorbent were well-fitted with a fractional-order kinetic model. The modeling analysis found the influence of diffusion resistance on the adsorption is more significant than that of the driving force. The CO2 capacity of CPEI remained almost constant during the temperature swing adsorption/desorption cycles.